Effects of Intensity of Facial Expressions on Amygdalar Activation Independently of Valence - Lin, Huiyan; Mueller-Bardorff, Miriam; Mothes-Lasch, Martin; Buff, Christine; Brinkmann, Leonie; Miltner, Wolfgang H. R.; Straube, Thomas (Frontiers in Human Neuroscience, 2016)
For several stimulus categories (e.g., pictures, odors and words), the arousal of both negative and positive stimuli has been shown to modulate amygdalar activation. In contrast, previous studies did not observe similar amygdalar effects in response to negative and positive facial expressions with varying intensity of facial expressions. Reasons for this discrepancy may be related to analytical strategies, experimental design and stimuli. Therefore, the present study aimed at re-investigating whether the intensity of facial expressions modulates amygdalar activation by circumventing limitations of previous research. Event-related functional magnetic resonance imaging (fMRI) was used to assess brain activation while participants observed a static neutral expression and positive (happy) and negative (angry) expressions of either high or low intensity from an ecologically valid, novel stimulus set. The ratings of arousal and intensity were highly correlated. We found that amygdalar activation followed a u-shaped activation pattern with highest activation to high intense facial expressions as compared to low intensity facial expressions and to the neutral expression irrespective of valence, suggesting a critical role of the amygdala in valence-independent arousal processing of facial expressions. Additionally, consistent with previous studies, intensity effects were also found in visual areas and generally increased activation to angry vs. happy faces were found in visual cortex and insula, indicating enhanced visual representations of high arousing facial expressions and increased visual and somatosensory representations of threat.